Effect of silver diamine fluoride and potassium iodide on residual bacteria in dentinal tubules. (March 2015) - Hamama, HH; Yiu, CK; Burrow, MF
Abstract Background This study evaluated the antimicrobial effect of a silver diamine fluoride (SDF)/potassium iodide (KI) product (Riva Star) on the viability of intratubular bacteria. Methods Forty‐five dentine discs prepared from caries‐free maxillary premolars were randomly divided into nine groups. Group 1 (negative control) contained non‐infected sound dentine discs. The remaining discs were infected with Streptococcus mutans suspension and received dentine treatments as follows: Group 2 (positive control), discs were left untreated; Group 3 SDF/KI (Riva Star); Group 4 chlorhexidine (CHX); Group 5 CHX + SDF/KI; Group 6 Carisolv; Group 7 Carisolv + SDF/KI; Group 8 Papacarie, and Group 9 Papacarie + SDF/KI. The discs were then fractured into two halves, stained with fluorescent LIVE/DEAD stain and observed using confocal laser scanning microscopy. Results SDF/KI exhibited a potent antibacterial effect, as represented by a significantly higher percentage of dead bacteria, in comparison with Carisolv and Papacarie (p < 0.05). The application of SDF/KI following Carisolv and Papacarie chemomechanical caries removel gels significantly reduced the viability of intra‐tubular bacteria in these groups. Conclusions The use of the silver diamine fluoride/potassium iodide product is effective in reducing the numbers of S. mutans in dentinal tubules infected with this organism.